2021
DOI: 10.1108/pijpsm-07-2021-0093
|View full text |Cite
|
Sign up to set email alerts
|

Perceived organizational support and its interaction with voice on police officers' organizational cynicism, stress and emotional exhaustion

Abstract: PurposeAmong a sample of 281 active-duty Canadian police officers, the current study investigated whether perceived organizational support (POS) would predict officers' organizational cynicism, stress and emotional exhaustion three months later. The moderating influence of officer voice on these relationships was also examined.Design/methodology/approachIn collaboration with a large policing organization, online surveys collecting quantitative data and soliciting open-ended comments were administered to office… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 75 publications
2
7
0
Order By: Relevance
“…spirituality) may promote the mental health of police trainees, and the findings may inspire the development of novel mental health promotion programs for police officers. Spirituality may play a positive role in helping police officers rediscover the meaning and value in police work, prompt officers to strive for their professional goals and social responsibility, and hence enhance their tolerance to fatigue and distress in daily work (Koenig, 2009), which might contribute to PIJPSM 46,3 promoting police officers' work engagement and performance as well as preventing emotional exhaustion and job burnout (Riedy et al, 2020;Smith et al, 2022).…”
Section: Spirituality and Mental Healthmentioning
confidence: 99%
“…spirituality) may promote the mental health of police trainees, and the findings may inspire the development of novel mental health promotion programs for police officers. Spirituality may play a positive role in helping police officers rediscover the meaning and value in police work, prompt officers to strive for their professional goals and social responsibility, and hence enhance their tolerance to fatigue and distress in daily work (Koenig, 2009), which might contribute to PIJPSM 46,3 promoting police officers' work engagement and performance as well as preventing emotional exhaustion and job burnout (Riedy et al, 2020;Smith et al, 2022).…”
Section: Spirituality and Mental Healthmentioning
confidence: 99%
“…Employees who demonstrate high cynicism are typically pessimistic, quick to fault the organization, liberal in blaming others for poor work or procedural outcomes, and highly critical of organizational processes (Enciso et al. , 2017; Smith et al. , 2021).…”
Section: Theory and Hypothesis Developmentmentioning
confidence: 99%
“…Employees who demonstrate high cynicism are typically pessimistic, quick to fault the organization, liberal in blaming others for poor work or procedural outcomes, and highly critical of organizational processes (Enciso et al, 2017;Smith et al, 2021). This kind of negative behavior stifles change (Stanley et al, 2005) and results in a reduction in championing behavior (Herscovitch and Meyer, 2002).…”
Section: Theory and Hypothesis Developmentmentioning
confidence: 99%
“…Similarly, in a study of frontline workers in the hospitality industry, Walters and Raybould (2007) found significant relationships between POS and each of the three burnout dimensions examined, i.e., exhaustion, cynicism, and personal efficacy. Further evidence is provided by Anomneze et al (2016), who reported a link between POS and emotional exhaustion among teachers; by Hosseini (2021), who reported a significant relationship between levels of organizational support and job stress; and, most recently, by Smith et al (2022), who found that POS predicted emotional exhaustion, stress, and cynicism three months later in a study with active-duty Canadian police officers.…”
Section: Direct Effect Of Pos On Strainsmentioning
confidence: 98%
“…The direct effect of POS and well-being has been studied frequently in the past two decades under both normal working conditions and during high stress work situations. For example, POS has been shown to operate at all levels of POS when investigated with fatigue (Cropanzano et al, 1997), job stress (Jones et al, 1995;Asad & Khan, 2003); burnout (Asad & Khan, 2003;Armstrong-Stassen, 2004), emotional exhaustion (Fiksenbaum et al, 2006;Anomneze et al, 2016;Smith et al, 2022), anger (Fiksenbaum et al, 2006;O'Neill et al, 2009), and sleep problems (Caesens et al, 2014).…”
Section: Direct Effect Of Pos On Strainsmentioning
confidence: 99%